Effect of Influencer Marketing and Green Marketing on Brand Awareness of Traditional Culinary SMEs in West Java - Asep Muhamad Ramdan; Leonita Siwiyanti; Kokom Komariah; Muhamad Arief Ramdhany (Jurnal Ilmu Sosial dan Humaniora, 2023)
The brand awareness of traditional culinary Small Medium Enterprises (SMEs) in West Java can arise from green marketing initiatives triggered by influencer marketing and company commitment. In this article, we explore the effect of influencer marking and green marketing moderated by consumer trust in influencers on SMEs' brand awareness. The population framework in this study is more than 26,000 traditional culinary SMEs in West Java. The representative sample is 380 based on the calculation. Inferential analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM). The results find that influencer marketing positively affects both green marketing initiatives and brand awareness. Green marketing initiatives positively influence brand awareness, and consumer trust in influencers enhances brand awareness. Consumer trust in influencers also moderates the effects of both influencer marketing and green marketing initiatives on brand awareness. Additionally, green marketing initiatives mediate the relationship between influencer marketing and brand awareness, serving as a channel through which influencer marketing impacts brand awareness. These findings highlight the importance of influencer marketing, green marketing initiatives, and consumer trust in shaping brand awareness in a sustainable context.